Reliability, agreement, and diagnostic accuracy of the Modified Lateral Scapular Slide test. (August 2016) - Shadmehr, A.; Sarafraz, H.; Heidari Blooki, M.; Jalaie, S.H.; Morais, N.
Abstract: Background: The Lateral Scapular Slide Test is a static test used in clinical settings to assess medio-lateral inferior angle displacement and scapular asymmetry at three different degrees of shoulder abduction. However, there is no evidence in the literature about the reliability and diagnostic accuracy of a modified LSST (arm elevation in the scapular plane with loading) in a symptomatic population. Objective: To assess the intra- and inter-rater reliability, agreement, and diagnostic accuracy of the MLSST ​ (Modified Lateral Scapular Slide Test) in subjects with and without shoulder symptoms. A new test position is examined, in which the arm is held in 90° of elevation in the scapular plane with 1 kg load. Design: Within day intra- and inter-rater reliability, agreement, and diagnostic accuracy study. Method: Participants included 25 (42 ± 2.7 years) subjects with shoulder symptoms and 25 (40 ± 2.1 years) asymptomatic control subjects. Two raters, blinded to each other's outcomes, measured the distance between the inferior scapular angle and T7 at arms by the side, hands on hips and 90° of arm elevation in the scapular plane with 1 kg load. Measurements were performed twice, bilaterally. Intraclass correlation coefficient (ICC), minimal detectable change (MDC95% ) and diagnostic accuracy were calculated. Results: The ICCs for intra- and inter-rater reliability were good to high in both shoulders of symptomatic and asymptomatic groups. The MDC95% in the symptomatic group ranged between 0.67 and 1.40 cm in the symptomatic shoulder and 0.72–1.16 cm in the asymptomatic shoulder. The asymptomatic group presented a MDC95% ranging between 0.63 and 1.52 cm in the dominant and 0.60–1.41 cm in the non dominant shoulder. Positive and negative likelihood ratios ranged between 0.67–5.50 and 0.81–1.11, respectively. Conclusion: The MLSST had good reliability and agreement properties to assess scapular position in both groups. However, no test position had clinical utility as a diagnostic criterion for shoulder pathology. Highlights: The Modified Lateral Scapular Slide Test showed acceptable reliability in practice. Clinical utility of Modified Lateral Scapular Slide test was low. Generalizability of MLSST is limited in the clinical setting.